(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The given article is dedicated to study the English borrowings, which are actively used in the formation of Uzbek culinary lexicon. In the example of the English culinary name “pudding”, dynamics of borrowed words have been analyzed.